Parendodontic surgery to remove a periapical cyst: case report (Research, Society and Development, 2022)
Objective: To describe a clinical case in which endodontic surgery was performed to remove a periapical cyst, associated with apicectomy and retrograde MTA obturation. Methodology: After signing the informed consent by the patient, an analytical and descriptive clinical case report was carried out at the Faculty of Dentistry of Pernambuco, FOP – UPE. Results: A 19-year-old male patient, without underlying diseases, sought clinical care at the Faculty of Dentistry of Pernambuco to with the aim of completing the endodontic treatment in a tooth with an extensive periapical lesion and open apex, a as the filling was not possible due to drainage of a purulent collection via the root canal. After requesting and analyzing the, it was decided to perform a paraendodontic surgery performed for enucleation of the periapical cyst and, after cutting the apex, retrograde obturation with MTA was performed in order to perform the obturation in the next session. of the root canal. Final considerations: It was found that paraendodontic surgery combined with apicectomy and retrograde filling with MTA determined the success of the treatment, resulting in the repair of periapical bone radiotransparency.